SYNTHESIS OF MEMBRANES FROM PILLARED CLAY FeCl3 FOR SEAWATER DESALINATION APPLICATION - Muslimin, Muslimin; Darmawan, Adi; Lusiana, RA. (Jurnal Sains Dasar, 2018)
Synthesis of membranes has been done using pillared clay FeCl3for desalination application. Pillared clays FeCl3were synthesized via a sol-gel method using [OH] / [Fe] 0.25, 0.5, 1, 2, 2.5. Formed sol-gel was furnace  on 600oC for 2 hours. The membranes which were cooled at room temperature for 3 days then tested filtration of seawater. The results showed that membrane pillared clays FeCl3 with a ratio [OH] / [Fe] 0.25  reached filtration purity 99.99% with the initial TDS 27.58 ppm and  resulted rejection TDS 00.22 ppm after filtration. Membrane with ratio [OH] / [Fe] 0.5 reached filtration purity 80%, with initial TDS   27.58 ppm  and resulted rejection TDS  11.76 ppm,  while membranes with ratio [OH] / [Fe] 1,2 and 2,5 was broken during the filtration proces, its resulted very small rejection. Keywords: membrane, pillared clay, FeCl3, Seawater desalination